DAYA TOLAK INFUSA DAUN PANDAN WANGI ( Pandanus amaryllifolius Roxb. ) TERHADAP PELETAKAN TELUR NYAMUK AEDES SPP. AEDES SPP. AEDES SPP. - ., Anggie Cahyadi (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Aedes spp larval resistance against chemical insecticide has beenreported in many country. The new methods that can be used to control themosquito populations as a dengue fever vector and alternative compound whichis safe for environtment and cant cause the resistance need to be found. Pandanleaves have aromatic fragrant that can be expected as a oviposition deterrenteffect against Aeses spp mosquito.Objective. To know oviposition deterrent effects and optimum consentration ofpandan leaves(Pandanus amaryllifolius Roxb.)infusa against Aedes spp.Methodology. This research was an experimental research using six groups ofconcentration. There was 0 mL/L(control), 3 mL/L, 3,5 mL/L, 4 mL/L, 4,5 mL/Land 5 mL/L. Every groups would be repeated by fourth. Ovitraps with differentconcentration of pandan leaves infusa placed at research location. The mosquitoeggs that caught at the ovitrap would be counting and identifying in thelaboratorium. Data was analyzed using One Way Anova test via computerprogram SPSS 19.0 and then continued by LSD test with 95% confidence level.Result. The repellency percentage at 3 mL/L concentration is 30.35%; 3,5 mL/Lis 55.35%; 4 mL/L is 65.17%; 4,5 mL/L is 82.14% and 5 mL/L is 100% withsignificancy value is 0,000(p<0,05).Conclusion. Pandan leaves(Pandanus amaryllifolius Roxb.)infusa hasoviposition deterrent effects against Aedes spp. and the optimum concentration isat 4,5 5 mL/L.Keywords: Oviposition deterrent effects, Pandanus amaryllifolius Roxb.,oviposition, Aedes spp.